1977
DOI: 10.1002/1097-0142(197702)39:2<447::aid-cncr2820390213>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer as seen in giant histologic sections

Abstract: Giant sections from cystectomy specimens in 45 cases of bladder cancer were examined microscopically after en bloc fixation and processing. There were 35 transitional cell, seven squamous cell, and three mixed transitional cell and squamous carcinomas. Broad front invasion was associated with papillary and superficial tumors while tentacular invasion was associated with solid tumors and a generally poorer prognosis. Carcinoma in situ merged with the invasive cancer in 33 cases, and neoplasia in these cases ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(19 citation statements)
references
References 16 publications
2
16
1
Order By: Relevance
“…However, these findings should be cautiously analyzed. A form of explaining this lack of statistic significance is the small number of patients with this finding when compared to other series (1,11,14). This could be well illustrated by the survival curves that have shown a trend to an unfavorable evolution among patients with PNI.…”
Section: Commentsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, these findings should be cautiously analyzed. A form of explaining this lack of statistic significance is the small number of patients with this finding when compared to other series (1,11,14). This could be well illustrated by the survival curves that have shown a trend to an unfavorable evolution among patients with PNI.…”
Section: Commentsmentioning
confidence: 83%
“…The PNI is reported in 6.8 to 47.7% of the patients with transitional cell carcinoma (TCC) of the bladder treated with radical cystectomy (1,2,(11)(12)(13)(14). While in the majority of such studies the PNI is related to disease-free survival (12,14) and global survival (2,12) only in univariate analysis, others have demonstrated that the PNI also presents a prognostic value in multivariate analysis (13).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all non-invasive urothelial carcinomas are grade 1 or 2 in the three-tier WHO 1973 classification [8,15,109]. Approximately 70% of these tumors are non-invasive (stage 0; pTa), and 30% invade the lamina propria (stage A; pT1) [32].…”
Section: Invasive Papillary Urothelial Carcinomamentioning
confidence: 99%
“…These guidelines leave it to the pathologists to select those of the listed areas that may be expected to contain microscopic lesions [24]. This method of selection, however, is only of limited value, especially in the case of formalin-fixed samples [35]. Due to the recognition of the significance of the additional information to be gained for clinical use, the need for a more precise determination of the pathological processing technique of cystectomy specimens arose fifteen years ago [36].…”
Section: Materials Consumption and Costsmentioning
confidence: 99%
“…Due to the recognition of the significance of the additional information to be gained for clinical use, the need for a more precise determination of the pathological processing technique of cystectomy specimens arose fifteen years ago [36]. The first trial with a relatively large case number was conducted by Soto et al They inflated the bladder with celluloid, and applied a lengthy procedure only to 45 radical cystectomy preparations that could be examined as a whole over the fifteen-year period [35]. The most commonly applied method is the stepsectioning, which begins with the urinary bladder being opened through the urethra by a cut along the anterior wall, stretched on a corkboard and fixed.…”
Section: Materials Consumption and Costsmentioning
confidence: 99%